Access to public information in government agencies and archives : new e-services for archives: results from user and expert survey - Runardotter, Mari; Jonsson, Östen; Eiríksdóttir, Helga Jóna; Sighvats, Julía Pálmadóttir; Sigurðsson, Njörður; Djupdahl, Mattias; Geber, Magnus; Nurme, Birgit; Aas, Kuldar; Ruusalepp, Raivo (Luleå tekniska universitet, Innovation och Design, 2011)
The on-going transformation process of e-government and e-services permeates most sectors in society. Initiatives are taken not only by public agencies, but also by the private sector, research communities and individuals. This paper focuses on e-services in the cultural heritage sector and presents the results from a joint networking project of archives and academia from Estonia, Iceland and Sweden - the Access to Public Information in Governmental Agencies and Archives (APIS) project. Godkänd; 2011; 20121003 (marrun)